Crystal structure of N‐terminal degron‐truncated human glutamine synthetase. Issue 11 (2nd November 2021) - Chek, Min Fey; Kim, Sun-Yong; Mori, Tomoyuki; Kojima, Hisayuki; Hakoshima, Toshio
Abstract : The crystal structure of N‐terminal degron‐truncated human glutamine synthetase was determined at 2.95 Å resolution, which revealed that the N‐degron is not essential for decamer formation. The study also investigated the roles of N‐degron in oligomerization and enzymatic activities through biochemical analyses. Abstract : Glutamine synthetase (GS) is a decameric enzyme that plays a key role in nitrogen metabolism. Acetylation of the N‐terminal degron (N‐degron) of GS is essential for ubiquitylation and subsequent GS degradation. The full‐length GS structure showed that the N‐degron is buried inside the GS decamer and is inaccessible to the acetyltransferase. The structure of N‐degron‐truncated GS reported here reveals that the N‐degron is not essential for GS decamer formation. It is also shown that the N‐degron can be exposed to a solvent region through a series of conformational adjustments upon ligand binding. In summary, this study elucidated the dynamic movement of the N‐degron and the possible effect of glutamine in enhancing the acetylation process.